Analisis Pertumbuhan dan Tingkat Kematangan Gonad Ikan Buntal (Tetraodon Fluviatilus) - Sunarni Sunarni; Sisca Elviana; Stenly M.B.S Wairara (Universitas Musamus, Merauke, Papua, 2020)
The aim of this study was to analyze the growth and maturity level of puffer fish (Tetraodon fluviatilus). This research was conducted in October-December 2017. The research site consisted of two places, namely sampling conducted in two locations of the brackish waters of Merauke Regency while the analysis and identification of growth and maturity level of the gonads was carried out in the laboratory of Department of Aquatic Resources Management, Universitas Musamus. Sampling was conducted at Lampu Satu Beach (station I) and Payum beach (station II) using descriptive methods and survey techniques. Sampling was carried out six times at each station for three months. To find out the growth and maturity level of pufferfish gonads, an analysis of growth patterns, condition factors, sex ratio and gonad maturity levels was performed. The results of the study showed that the growth of puffer fish at Station I was negative allometric while at Station two it was positive allometric. The mean value of the puffer fish condition at Station I was 0.0499 while that at Station II was 0.7062. Gonadal maturity level (TKG) at station I and II are at TKG I, at station I is 79.04% while at station II is 69.77%. Based on the results of research conducted it can be concluded that the growth patterns and TKG at Station I are better than Station II.